Juvenile Probation Officer Perceptions of Parental Involvement in Juvenile Probation and With Contingency Management - Ingel, Sydney N. (Criminal justice and behavior, 2023)
Probation is a common sanction for youth substance users, and as such, juvenile probation officers (JPOs) shoulder much of the burden for treatment and rehabilitation. To improve youth outcomes and alleviate some of the burden, JPOs may seek parental involvement in the probation and substance use desistance processes. Using focus group data, we analyzed JPO perceptions of the role parents play in contingency management (CM)—an incentive system designed to produce and reward decreased substance use—and whether they perceived any value in CM. We found that most JPOs perceived parental involvement as critical to the success of both substance use treatment and CM for youth. Our findings also suggest JPOs found parental involvement in CM valuable given that CM was employed on nonstudy clients and future clients. This has implications for the practicality and sustainability of CM as a youth probation intervention.